Effect of Product Quality, Service Quality, Application Quality, and Familiarity on Trust in E-commerce and Purchase Intention - Anureza, Zahra Tsabitha (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2025)
This study investigates the effects of product quality, service quality, application quality, and familiarity on consumer trust in e-commerce, and their subsequent impact on purchase intention. Using a quantitative survey of 305 Shopee users in Indonesia, the data were analyzed with Structural Equation Modeling (SEM-AMOS). Hypothesis testing revealed mixed results: product quality (H1) showed a positive but insignificant effect on trust, indicating that inconsistent product reliability reduces its role in fostering trust. In contrast, service quality (H2), familiarity (H3), and application quality (H4) were found to have significant positive effects on trust, emphasizing the importance of responsiveness, brand experience, and application usability in shaping consumer confidence. Furthermore, trust (H5) significantly and positively influenced purchase intention, confirming its role as a key mediating factor in online buying decisions. These findings highlight that while product quality remains essential, it is the combination of reliable service, user-friendly applications, and platform familiarity that most strongly strengthens e-commerce trust and increases purchase intention.